Independent Evaluation Office, Annual Report 2003. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2003)
This first Annual Report describes the activities of the IEO through the first full year of operation. The report provides a summary of the main findings and recommendations of the first three evaluation projects on the prolonged use of IMF resources, the role of the IMF in recent capital account crises, and the role of fiscal adjustment in IMF-supported programs. It also indicates the status of ongoing evaluation projects, and discusses several common themes emerging from the IEO's evaluations.